95 Investigating fibroblast involvement in vascular inflammation using co-culture models. (June 2018) - Wright, Kelly; Haycock, John; Francis, Sheila
Abstract : Introduction: Coronary heart disease is caused by the accumulation of fatty deposits within the vascular lining. This process often goes undetected until a patient becomes symptomatic (e.g. myocardial infarction); consequently, current treatments are primarily aimed at symptomatic relief. However, it is necessary to understand the inflammatory processes that underpin atherogenesis, enabling the development of novel therapeutic strategies. ICAM-1 is up-regulated during inflammation to aid leukocyte extravasation and is expressed by numerous cell types. Moreover, the involvement of the adventitial fibroblast is becoming increasingly popular, thus ICAM-1 was used as a marker to study the augmentation of the inflammatory response in HUVEC/HUASMC/NHDF co-cultures. Methods: 25 U/mL human recombinant TNF-α was used to stimulate HUVEC, HUASMC and NHDF in 2D monoculture and co-culture arrangements, fixing samples every 3 hours for up to 12 hours before immunolabelling for ICAM-1. T-tests were used to determine any significant differences in ICAM-1 expression, and the relationship between cell ratio and ICAM-1 expression was examined. Results: ICAM-1 expression was significantly up-regulated upon the introduction of TNF-α under all conditions in HUVEC (figure 1). However, baseline expression was increased when co-cultured with both NHDF (2.0 vs 1.3, p<0.001) and HUASMC (6.5 vs 1.3, p<0.001). This meant that ICAM-1 expression at 12 hours was also significantly higher in co-culture with NHDF (8.3 vs 5.2, p<0.001) and HUASMC (11.0 vs 5.2, p<0.001). Moreover, there was a moderate relationship between HUVEC ICAM-1 expression and the cell ratio when in co-culture with NHDF, where decreasing NHDF resulted in decreased ICAM-1 in HUVEC (R2=0.45). TNF-α caused an increase in ICAM-1 expression in NHDF under monoculture conditions (Fig. 2); this up-regulation was significantly reduced in co-culture conditions with HUVEC (1.7 vs 5.1, p<0.001). A similar trend was observed when in co-culture with HUASMC (2.7 vs 5.1, p<0.001), except the baseline expression of ICAM-1 was also increased (2.8 vs 1.1, p<0.001). Constitutive production of ICAM-1 was observed in HUASMC, whereby the introduction of TNF-α or additional cell types resulted in no significant differences after 12 hours (not shown). Discussion/conclusion: It appears that a complex communication network exists between the endothelial cell, smooth muscle cell and fibroblast to control the vascular inflammatory response that underpins atherogenesis. Whilst the smooth muscle cell enhanced ICAM-1 expression on endothelial cells prior to the addition of TNF-α, the largest change in ICAM-1 appeared when the endothelial cells were co-cultured with fibroblasts. Though these experiments were carried out in 2D, evidence suggests that the fibroblast may contribute significantly to the expression of ICAM-1 in vasculature. Developing a 3D model to study this further will yield the significance of these cellular interactions to the atherogenic inflammatory response.